PID Tuning for Robustness to Noise in DC Motor Angular Position Control System - Pambudi, Arga Dwi; Heryanto, M Ary; Wulandari, Sari Ayu (Jurnal Teknik Elektro Indonesia, 2025)
DC motor position control often encounters challenges related to noise interference, which can degrade system performance in industrial applications. This study evaluates the performance of PID controllers using tuning approaches based on Ziegler-Nichols and Cohen-Coon methods and develops an iterative tuning method based on system response evaluation to enhance robustness. Simulations were conducted in MATLAB/Simulink, integrating White Gaussian Noise and Sinusoidal Noise to test the system's resilience. Initial results showed that Ziegler-Nichols achieved the fastest rise time (0.006 s) but with a high overshoot (61.78%). Meanwhile, the Cohen-Coon method demonstrated lower overshoot (32.49%) but became unstable under noisy conditions. To address these weaknesses, parameter refinement for Kp, Ki, and Kd was performed using a trial-and-error approach. Final results indicated that the combination of Kp=25, Ki=100, and Kd=0.6 reduced the overshoot to 4.74%, settling time to 0.759 s, and maintained a low steady-state error (1.5%). This study highlights that the trial-and-error approach can enhance system robustness against noise while providing a practical solution for DC motor control systems in real-world applications.